Circulação extracorpórea e injúria renal aguda em cirurgia de revascularização do miocárdio - Simão, Antônio Felipe Leite (2022)
Introduction: The use of cardiopulmonary bypass (CPB) in cardiac surgery often causes acute kidney injury(AKI), which increases morbidity and mortality. Objectives: To evaluate the impact of CPB on renal function in patients undergoing coronary artery bypass graft (CABG) surgery, using new biomarkers. Methods: This is a prospective study with patients who underwent CABG from August 2019 to October 2020at the Walter Cantídio University Hospital (HUWC). Variables related to clinical, surgical and laboratory aspects were collected. The glomerular filtration rate was estimated using the CKD-EPI equation. The new biomarkers were urinary Nephrin, NGAL, MCP-1 and KIM-1. In serum, NGAL was evaluated. Results:A total of 30, 22 patients were evaluated. The mean age was 65 ± 8 years, and 68% were male. There was no statistical difference in clinical aspects between the groups (CABG with and without CPB), except for STS-score and ejection fraction (EF). Urinary Nephrine and NGAL and serum NGAL showed higher levels in the on-pump CABG group. In the intraoperative period, the on-pump CABG group had increased levels of urinary nephrine compared to the off-pump CABG group 2051.42 [1018.82 - 4166.25] vs 400 [27.59 - 1186.9] pg/mg-Cr , p=0.007), as well as for NGAL in urine ( 24 [13.28 - 31.58] vs 7.24 [4.55 - 14.18] ng/mg-Cr, p=0.036), and in serum 282.12 [232.5 - 312.25] vs 165.15 [126.16 - 186.42] ng/ml, p=0.030). In addition, urinary NGAL levels in patients undergoing on-pump CABG were correlated with a decrease in glomerular filtration rate in the first 48 hours after revascularization (Rho= -0.838, p=0.009).In addition, CPB showed an association between renal inflammation before (Rho= -0.766, p=0.027) and after surgery (Rho= -0.793, p=0.033), according to urinary MCP-1 levels, with a decrease in GFR in the first 48 hours. No significant correlation was observed in the off-pump group.Conclusion: The CPB used during CABG was associated with relevant impacts on renal function, such as podocyte and tubular injury, and its impairment in the short term.